2018
DOI: 10.1002/jso.24997
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long‐term outcomes of 530 esophageal squamous cell carcinoma patients with minimally invasive Ivor Lewis esophagectomy

Abstract: MIE Ivor Lewis is a safe and feasible procedure in ESCC patients. It offers satisfactory perioperative outcomes, rapid QOL improvement, and acceptable long-term oncologic survival. Adjuvant chemoradiotherapy may improve OS and DFS in advanced stage patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As to the one‐year overall survival rates, the statistical difference was relatively mild and the difference of one‐year DFS rate was not obvious while it became obvious in the third year. This may have been related to the timeliness of adjuvant therapy and postoperative tumor bed blood circulation disorders, which resulted from the operation damage that had not been completely rebuilt, thus leading to the increased proportion of hypoxic tumor cells . The increase in the proportion of hypoxic tumor cells was associated with decreased sensitivity to radiotherapy and reduced local delivery of chemotherapeutic drugs …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the one‐year overall survival rates, the statistical difference was relatively mild and the difference of one‐year DFS rate was not obvious while it became obvious in the third year. This may have been related to the timeliness of adjuvant therapy and postoperative tumor bed blood circulation disorders, which resulted from the operation damage that had not been completely rebuilt, thus leading to the increased proportion of hypoxic tumor cells . The increase in the proportion of hypoxic tumor cells was associated with decreased sensitivity to radiotherapy and reduced local delivery of chemotherapeutic drugs …”
Section: Discussionmentioning
confidence: 99%
“…This may have been related to the timeliness of adjuvant therapy and postoperative tumor bed blood circulation disorders, which resulted from the operation damage that had not been completely rebuilt, thus leading to the increased proportion of hypoxic tumor cells. 22,23 The increase in the proportion of hypoxic tumor cells was associated with decreased sensitivity to radiotherapy and reduced local delivery of chemotherapeutic drugs. [24][25][26][27] In this study, there were no differences in the overall recurrence and metastasis rates between the CRT and RT groups, which is opposite to the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HMIE using laparoscopy and thoracotomy presented no priority in short-term survival compared to those with OE. Wang et al reported that 6-year overall survival and disease-free survival were 44.7% and 46.1%, respectively, for MIE, indicating that MIE is safe[40]. A score-matched study showed that the 2-year overall survival rates based on same pathologic stage were similar between MIE and OE[41].…”
Section: Discussionmentioning
confidence: 99%